English: - - Pratiwi, Rianta; Sukardjo, Sukristijono; Widyastuti, Ernawati; Hafizt, Muhammad (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Segara Anakan mangrove waters is a lagoon surrounded by mangrove forests and muddy land. Mangrove forests have an ecological function such as spawning ground, nursery ground, and feeding ground for various biota. Mud crab is one of fishery commodities, which is important in Indonesia. Segara Anakan mangrove waters, is one of the fishing villages which catch mud crabs because of the high demand. The high demand for mud crabs needs to be balanced with the right management strategy, so that the population will not extinction. The purpose of this study is to determine the ecology of mud crab, Scylla serrata Forskål, 1775 and its fishery potential and also to explain the habitat population in the Segara Anakan mangrove forest. Many previous studies conducted by previous researchers. Environmental parameters, i.e. temperature, salinity, oxygen, light penetration, and nature of the bottom were also studied. Crabs were caught by traditional crab catch fishery called “Wadong” (fish pot). Around 6487 crabs were caught by “wadong”. The catch consisted of 2920 male crabs (45.02%) and 3567 female crabs (54.98%). The dominant size groups for males and females in terms of their carapace length (CL) were 35.00-40.00 mm and 43.00-106.00 mm, respectively. Females mature at smaller size, i.e. at 42.70 mm CL. Breeding takes places during June-July. CL weight relationship showed that males were heavier than females. The regression equations for both sexes are as follows: WF= 10-3 5.871 L2.4443 (r= 0.999) and WM= 10-4 4.043 L3.1035 (r= 0.999).